48V full hybrid, 48V mild hybrid, 48V BEV cars : markets, technology roadmap 2021-2041 : post COVID, capacitor assisted batteries, PV wrap, next rotating machines, parts, systems, features, trucks, buses /: markets, technology roadmap 2021-2041 : post COVID, capacitor assisted batteries, PV wrap, next rotating machines, parts, systems, features, trucks, buses. ([2020?]) - Harrop, Peter
No abstract available